NSCAs Performance Training Journal - New Training Methods (NSCAs Performance Training Journal, 2008)
The Grappler: The Reinvention of an Old Training Modality Vilayat Del Rossi: This article examines how to perform traditional, and not so traditional exercises on the grappler. Included is a sample program.